Influence of exercise order on maximum strength and muscle volume in nonlinear periodized resistance training - Spineti, J.; de Salles, B. F.; Rhea, M. R.; Lavigne, D.; Matta, T.; Miranda, F.; Fernandes, L.; Simao, R. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to examine the influence of exercise order on strength and muscle volume (MV) after 12 weeks of nonlinear periodized resistance training. The participants were randomly assigned into 3 groups. One group began performing large muscle group exercises and progressed to small muscle group exercises (LG-SM), whereas another group started with small muscle group exercises and advanced to large muscle group exercises (SM-LG). The exercise order for LG-SM was bench press (BP), machine lat pull-down (LPD), triceps extension (TE), and biceps curl (BC). The order for the SM-LG was BC, TE, LPD, and BP. The third group did not exercise and served as a control group (CG). Training frequency was 2 sessions per week with at least 72 hours of rest between sessions. Muscle volume was assessed at baseline and after 6 weeks and 12 weeks of training by ultrasound techniques. One repetition maximum strength for all exercises was assessed at baseline and after 12 weeks of training. Effect size data demonstrated that differences in strength and MV were exhibited based on exercise order. Both training groups demonstrated greater strength improvements than the CG, but only BP strength increased to a greater magnitude in the LG-SM group as compared with the SM-LG. In all other strength measures (LPD, TE, and BC), the SM-LG group showed significantly greater strength increases. Triceps MV increased in the SM-LG group; however, biceps MV did not differ significantly between the training groups. In conclusion, if an exercise is important for the training goals of a program, then it should be placed at the beginning of the training session, regardless of whether or not it is a large muscle group exercise or a small muscle group exercise.